From the military to college and beyond: Growing a culturally sensitive program to support veteran success. Issue 5 (17th January 2020) - Ulrich, Stefanie; Freer, Benjamin D.
Abstract: This paper addresses the unique characteristics of veterans and the role military culture continues to play for post‐service veterans. We describe a series of programs developed to provide critically important assistance to current and recent student veterans by connecting them to a network of veteran peers and mentors. Through a discussion of psychological distress and healing, stigma, and the challenges of college, we hoped to galvanize student veterans to recognize the value of psychological well‐being. We additionally offer suggestions, based on years of work with veterans, on the development of programs and the provision of clinical services for the veteran community.